Early Rome myth and society : a sourcebook - Neel, Jaclyn (Blackwell sourcebooks in ancient history., 2017)
The scholarly community has become increasingly aware of the differences between Roman myths and the more familiar myths of Greece. Early Rome: Myth and Society steps in to provide much-needed modern and accessible translations and commentaries on Italian legends. This work examines the tales of Roman pre-and legendary history, discusses relevant cultural and contextual information, and presents author biographies. This book offers updated translations of key texts, including authors who are often absent from classical mythology textbooks, such as Dionysius of Halicarnassus and Servius. Editor Jaclyn Neel debunks the idea that Romans were unimaginative copyists by spotlighting the vitality and flexibility of Italian myth, particularly those parts that are less closely connected to Greek tales, such as the story of Caeculus of Praeneste. Finally, by calling attention to the Italian rather than Roman nature of the collection, this book suggests that Roman culture was broader than the city itself. This important work offers: Up-to-date and accessible translations of Roman and Italic legends from authors throughout antiquity ; Examination of compelling tales that involve the Roman equivalent of Greek 'heroes' ; Unique view of the strength and plasticity of Roman and Italic myth, particularly the parts less closely connected to familiar Greek tales ; Intelligent discussion of relevant cultural and contextual information Argument that Roman culture reached far beyond the city of Rome Fresh and readable, Early Rome: Myth and Society offers essential reading for students of ancient Rome as well as those interested in Roman and Greek mythology.